Increased Resistance to Malaria in Mice with Methylenetetrahydrofolate Reductase (Mthfr) Deficiency Suggests a Mechanism for Selection of the MTHFR 677C>T (c.665C>T) Variant. Issue 5 (31st March 2014) - Meadows, Danielle N.; Pyzik, Michal; Wu, Qing; Torre, Sabrina; Gros, Philippe; Vidal, Silvia M.; Rozen, Rima
<x xml:space="preserve">Abstract</x> The map shows worldwide frequencies for homozygosity of the MTHFR 677C>T (c.665C>T) polymorphism, which is associated with enzymatic deficiency and increased risk for several complex traits. We explored the possibility of a selective advantage for this polymorphism by infecting Mthfr‐deficient and MTHFR‐overexpressing mice with P. berghei ANKA (cerebral malaria). We identified increased and decreased resistance, respectively, for these mice and suggest that this polymorphism may have reached high frequencies in malaria‐endemic regions through positive selection. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>